The Levels of Critical Thinking for Secondary Schools Students and Its Relationship with Many Variables (A Field Study in The Secondary Schools in Lattakia City) - Jnad, Rawaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aimed at investigating the level of critical thinking skills for the tenth grade students in light of the variables of sex and specialization (scientific - literary). The researcher used a test of (Watson and Glaser) for critical thinking. This test contains (75) items distributed to five axes; every axes represents a skill of critical thinking. These skills are : (deduction, extrapolation, explanation, evaluation of reasoning and knowing of hypotheses). The sample consisted of (277) students from public schools in the city of Lattakia. The results showed: Students have low level in critical thinking in general; and in the sub-skills as well. Students scored (52%) on Test of (Watson and Glaser) for critical thinking. This percent is less than known criteria which is (60%). The results indicated that there were no statistically significant differences in the level of critical thinking attributed to sex variable(Males and females almost have the same level of critical thinking). The results indicated that there were statistically significant differences in the level of critical thinking attributed to specialization variable in favor of scientific branch students. Many suggestion were introduced in the light of results such as training students to use of critical thinking skills.